2023
DOI: 10.3390/economies11030077
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of the Internal Control System on the Relationship between the Accounting Information System and Employee Performance in Jordan Islamic Banks

Abstract: The goal of the current study is to determine how the internal control system (ICS) in Jordanian Islamic banks affects the link between the accounting information system (AIS) and employee performance (EP). The study’s target audience is actual Jordanian Islamic Bank workers, and a sample of 92 respondents, representing a response rate of about 70.22%, was selected from a total of 131 participants, themselves divided among 105 branches of Islamic Banks in Jordan. According to the data, there is a clear correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Social and economic globalization, fewer clients and these elements taken together lead to greater competition in today's corporate environment (Almatarneh, Ineizeh, Jarah, & Al-Zaqeba, 2022). Companies are using new methods of company management to address the problem as the environment becomes more complicated (Jarah, Zaqeeba, Al-Jarrah, Al Badarin, & Almatarneh, 2023). HRM and TQM are two of these pillars of greater competitiveness that work together to improve products and processes by integrating suppliers and consumers (Alfalla, García, & Lopez, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social and economic globalization, fewer clients and these elements taken together lead to greater competition in today's corporate environment (Almatarneh, Ineizeh, Jarah, & Al-Zaqeba, 2022). Companies are using new methods of company management to address the problem as the environment becomes more complicated (Jarah, Zaqeeba, Al-Jarrah, Al Badarin, & Almatarneh, 2023). HRM and TQM are two of these pillars of greater competitiveness that work together to improve products and processes by integrating suppliers and consumers (Alfalla, García, & Lopez, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a higher probability that at a given opportunity, employees may rebel against oppressive hard controls. Interesting findings by Jarah, Zaqeeba [34] establish that misapplication of relevant controls are the causes of ineffective risk management. Finally, the most detrimental limitation of formal control occurs when two or more circumvent the purpose of controls [14], usually for motivated by greed, mistrust and lack of integrity.…”
Section: Limitations Of Formal Controlsmentioning
confidence: 99%
“…Accounting information systems have a significant effect on the improvement of corporate financial management. Literature [11] proposed that the application of an accounting information system improves the timeliness and accuracy of accounting information, and the construction of an accounting information system is an effective means for modern enterprises to improve their financial management capabilities. Literature [12] proposed the scope of application of accounting information systems in Chinese enterprises at this stage and found that although Chinese enterprises have made certain achievements in the construction of accounting informatization, the degree of accounting informatization is relatively low compared with developed countries.…”
Section: Introductionmentioning
confidence: 99%